I dati INVALSI come strumento per l'innovazione e il miglioramento scolastico IV Seminario "I dati INVALSI: uno strumento per la ricerca e la didattica" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
The Improvement Plan (better known as PdM, that is Piano di Miglioramento) was introduced in school agenda in 2015. Since then, both teachers and administrative staff have worked in a process of change and enhancement in two main areas: teaching/learning and organization/management ones. Consequently, it began to flourish implementing projects in order to find the best solutions to reach the main school goal: providing the educational success to all students, with respect for their several differences. This book collects papers, submitted at IV edition of the Seminar "INVALSI data: a research and teaching tool" held in Rome in November 2019, by both teachers and researchers to debate and deepen this topic, sharing ideas, suggestions, and experiences. INVALSI data could be a useful tool to find new paths to help schools in a permanent improving process, indeed.